Plasma accelerator with closed electron drift and open walls - Goncharov, A.; Dobrovolsky, A.; Najko, L.; Najko, I.; Litovko, I. (Вопросы атомной науки и техники, 2015)
We present the original approach to use plasma accelerators with closed electron drift and open walls for creating effective lens with positive space charge. In paper describes one-dimensional model and simplest analytical solutions following from it. The results of the numerical calculation and some experimental investigations data are presented also.